Influenza Virus Specific CD8+ T Cells Exacerbate Infection Following High Dose Influenza Challenge of Aged Mice. (26th September 2013) - Parzych, E. M.; DiMenna, L. J.; Latimer, B. P.; Small, J. C.; Kannan, S.; Manson, B.; Lasaro, M. O.; Wherry, E. J.; Ertl, H. C.
Abstract : Influenza viruses cause severe illnesses and death, mainly in the aged population. Protection afforded by licensed vaccines through subtype-specific neutralizing antibodies is incomplete, especially when the vaccine antigens fail to closely match those of the circulating viral strains. Efforts are underway to generate a so-called universal influenza vaccine expressing conserved viral sequences that induce broad protection to multiple strains of influenza virus through the induction of CD8 + T cells. Here we assess the effect of a potent antiviral CD8 + T cell response on influenza virus infection of young and aged mice. Our results show that CD8 + T cell-inducing vaccines can provide some protection to young mice, but they exacerbate influenza virus-associated disease in aged mice, causing extensive lung pathology and death.